2019
DOI: 10.1177/1352458519872889
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of multiple sclerosis with rituximab: A multicentric Italian–Swiss experience

Abstract: Background: Rituximab, an anti-CD20 monoclonal antibody leading to B lymphocyte depletion, is increasingly used as an off-label treatment option for multiple sclerosis (MS). Objective: To investigate the effectiveness and safety of rituximab in relapsing–remitting (RR) and progressive MS. Methods: This is a multicenter, retrospective study on consecutive MS patients treated off-label with rituximab in 22 Italian and 1 Swiss MS centers. Relapse rate, time to first relapse, Expanded Disability Status Scale (EDSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…Recommended dose for ocrelizumab is 600 mg intravenous every 6 months, with a fixed schedule, independent of age and Body mass Index (BMI). Otherwise rituximab has different administration protocols, usually based on CD20 repopulation count (Zecca et al, 2019) B-cell repopulation after depletion therapy discloses high inter-and intra-individual variance. Moreover, it has been demonstrated that body surface area could influence CD19 repopulation in Multiple Sclerosis patients treated with rituximab (Ellwardt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recommended dose for ocrelizumab is 600 mg intravenous every 6 months, with a fixed schedule, independent of age and Body mass Index (BMI). Otherwise rituximab has different administration protocols, usually based on CD20 repopulation count (Zecca et al, 2019) B-cell repopulation after depletion therapy discloses high inter-and intra-individual variance. Moreover, it has been demonstrated that body surface area could influence CD19 repopulation in Multiple Sclerosis patients treated with rituximab (Ellwardt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The MS therapeutic field has been recently widened by the approval of ocrelizumab (OCR) treatment as the first anti-CD20-depleting monoclonal antibody (mAb). 1 Rituximab (RTX), a first-generation anti-CD20 mAb, has also been adopted as an off-label treatment in MS, 2 , 3 and it is currently used as standard of care therapy in some European countries. 4 The standard treatment regimen of anti-CD20 mAbs usually consists of an “induction” phase, followed by regular fixed maintenance reinfusions (usually every 6 months).…”
mentioning
confidence: 99%
“…Ferner lieferten zahlreiche retrospektive Analysen und eine Subgruppenanalyse Hinweise dafür, dass Rituximab sowohl effektiv bei aggressiver RMS bzw. progressiver MS sein kann [33][34][35][36][37][38][39] als auch den MS-Therapien der 1. Generation (i.e.…”
Section: Zusammenfassung • Abstractunclassified